Ist der Anbau von Zuckerrüben als Biogassubtrat für Landwirte eine Alternative?: Ein Discrete-Choice-Experiment zur Ausgestaltung von Substrat-Lieferverträgen für Zuckerrüben; Is the Cultivation of Sugar Beets as a Biogas Substrate an Alternative for Farmers? A Discrete Choice Experiment for the Design of Substrate-supply-contracts for Sugar Beets - Saramena Sauthoff; Friederike Anastassiadis; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2016)
– In order to provide a sustainable renewable energy production in biogas plants, it is necessary to examine substrates apart from silage maize on their suitability and acceptance in society. In this context, sugar beets gain more and more importance for the production of biogas. To date, there have not been any studies on the attitude of farmers towards the alternative use of sugar beets in biogas plants. We, therefore, investigated how substrate supply contracts should be designed that farmers agree to cultivate sugar beets for biogas. Due to the lack of farm-level data, we conducted an online-survey including a Discrete Choice Experiment with 118 German farmers. Our results show that the participating farmers react with re-straint to contract sugar beets for biogas. If farmers opt for a supply contract of beet as biogas substrate, they prefer a short contract period and small-scale cultivation. A spring harvest of sugar beets is generally rejected.
Keywords: 330